1971
DOI: 10.1007/bf02531228
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon cooxidation in microbial systems

Abstract: This review summarizes the present status of hydrocarbon cooxidation in microorganisms. Hydrocarbons, which cannot be used for growth by many soil microorganisms, can be oxidized if present as co‐substrates in systems in which another substrate is furnished for growth. Paraffinic, cycloparaffinic and aromatic hydrocarbon cooxidations have been demonstrated. Most hydrocarbon cooxidation reactions seem to involve the incorporation of molecular oxygen by mono‐ and dioxygenases. From paraffinic hydrocarbons, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The biologically catalyzed production of industrial chemicals from petroleum-based raw materials provides a promising concept currently under study. Typifying the results of this research are the variety of oxidation products formed during metabolism of alkylbenzenes by bacteria and fungi (3,6,9). For example, Davis, Raymond, and co-workers (3,6) reported the production of phenylacetic acid from ethyland butylbenzene by species of Norcardia growing on aliphatic hydrocarbons.…”
mentioning
confidence: 81%
“…The biologically catalyzed production of industrial chemicals from petroleum-based raw materials provides a promising concept currently under study. Typifying the results of this research are the variety of oxidation products formed during metabolism of alkylbenzenes by bacteria and fungi (3,6,9). For example, Davis, Raymond, and co-workers (3,6) reported the production of phenylacetic acid from ethyland butylbenzene by species of Norcardia growing on aliphatic hydrocarbons.…”
mentioning
confidence: 81%
“…It accumulates in shrimp, clams, and other marine species. Dimethyl derivatives with 2-position occupancy were oxidized to the acid by Nocardia species (86). The oral toxicity in the rat appeared lower for the 1,6-dimethyl derivative than for the monomethyls (14).…”
Section: Production and Usementioning
confidence: 97%
“…The toxicity and the bioaccumulation increase with molecular weight. Nocardia cultures, isolated from soil, preferentially oxidized alkylnaphthalenes when methylated in the two positions (86). Methylnaphthalene can occur as the 1-or 2-, the alpha or the beta isomer.…”
Section: Production and Usementioning
confidence: 99%
See 1 more Smart Citation
“…Kitai et a1. * and Raymond et al 9 reported the incorporation of ion-exchange resin into culture media to "trap" toxic fermentation products in their hydrocarbon fermentations. Removal of the product in these cases permitted its continued synthesis.…”
Section: Introductionmentioning
confidence: 99%